Mesoscale Variability of Conditions Favoring an Iron‐Induced Diatom Bloom Downstream of the Kerguelen Plateau. Issue 5 (10th May 2018) - Della Penna, Alice; Trull, Thomas W.; Wotherspoon, Simon; De Monte, Silvia; Johnson, Craig R.; d'Ovidio, Francesco
Abstract: Heterogeneity in phytoplankton distribution is related to spatial and temporal variations in biogeochemical and ecological processes. In the open ocean, the interaction of these processes with meso‐ and submeso‐scale dynamics (1‐100 km, few days to months) gives rise to complex spatio‐temporal patterns, whose characterization is difficult without extensive sampling efforts. In this study, we integrate pigment sampling and multisatellite data to assess the link between iron enrichment and diatom dominance in the open ocean region east of the Kerguelen Islands (Indian Sector of the Southern Ocean). In this region, the High Nutrient Low Chlorophyll conditions typical of the Southern Ocean are alleviated by the transport of iron off the Kerguelen Plateau, resulting in a plume of chlorophyll that extends 1, 000 km downstream. We show that in situ concentrations of the diatom‐associated pigment fucoxanthin and ocean‐color‐derived estimates of diatom dominance correlate with the "water age", i.e., the time since the respective water parcel departed the Kerguelen Plateau. We propose a "threshold model" linking diatom ecological success and iron availability of downstream‐advected water parcels. The pattern of diatom dominance generated by this model predicts the extent and spatial structure of satellite‐based estimates at the regional scale (∼100s of km) and describes the mesoscale distribution of diatom dominance in the proximity of the plateau. However, the complexity of diatom dominance patterns further away from the plateau indicates that other physical and ecological mechanisms may drive phytoplankton dominance downstream. Key Points: Water parcels that have recently transited the Kerguelen Plateau favor diatom growth and dominance over other phytoplankton types Mesoscale advection of water parcels partially explains the distribution of diatom abundance and dominance in the proximity of the plateau The complexity of diatom dominance patterns at the mesoscale indicates that other mechanisms drive dominance further downstream